2021
DOI: 10.1093/ijpp/riab006
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of pharmacists prescribing for minor ailments in Ontario, Canada: a cost-minimization analysis

Abstract: Objectives The objective of this study was to use a decision-analytic model to examine the potential economic impact of establishing a remunerated programme for pharmacists prescribing for minor ailments (PPMA) in Ontario, Canada. Methods A novel decision tool was developed to assess the economic impact of pharmacists prescribing for upper respiratory tract infections (URTIs), contact dermatitis (CD) and conjunctivitis by per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The introduction of pharmacist prescribing programs for minor ailments in Canada over the last 15 years has brought about a profound transformation in the healthcare landscape, improving patient access to timely and cost-effective healthcare services, reducing the burden on primary care facilities, decreasing wait times and increasing patient satisfaction levels, leading to savings for governments. 49 , 50 , 51 However, the effects of these programs on patient self-care and self-medication remain uncharted territory. As of July 2023, pharmacist prescribing for minor ailments is a reality across all 10 Canadian provinces.…”
Section: Pharmacist Involvement In Minor Ailment Carementioning
confidence: 99%
“…The introduction of pharmacist prescribing programs for minor ailments in Canada over the last 15 years has brought about a profound transformation in the healthcare landscape, improving patient access to timely and cost-effective healthcare services, reducing the burden on primary care facilities, decreasing wait times and increasing patient satisfaction levels, leading to savings for governments. 49 , 50 , 51 However, the effects of these programs on patient self-care and self-medication remain uncharted territory. As of July 2023, pharmacist prescribing for minor ailments is a reality across all 10 Canadian provinces.…”
Section: Pharmacist Involvement In Minor Ailment Carementioning
confidence: 99%
“…46 Various studies in countries or provinces with public payers have indicated that pharmacist test and treat programs for minor ailments such as uncomplicated UTIs and hepatitis C would be cost saving for the public system, illustrating the potential benefits from widespread acceptance of pharmacists as providers and the creation of sustainable reimbursement models. 37,47,48 One pilot study in England where patients had to pay out of pocket for pharmacist UTI testing and treatment service that they could have received at a national healthcare system clinic free of charge found that the majority of patients who were tested and received treatment would have gone to their general practitioner if the pharmacy service was not available. 49 United States payers should be incentivized to promote pharmacy test and treatment services for acute conditions and advocate for the removal of regulatory barriers limiting the implementation of sustainable programs.…”
Section: Payer Perspectivementioning
confidence: 99%
“…A cost‐effective analysis comparing treatment of adult group A streptococcus pharyngitis patients by community pharmacists with various physician provider treatments found pharmacist treatment to be the most cost effective using a cost threshold of $55.56 46 . Various studies in countries or provinces with public payers have indicated that pharmacist test and treat programs for minor ailments such as uncomplicated UTIs and hepatitis C would be cost saving for the public system, illustrating the potential benefits from widespread acceptance of pharmacists as providers and the creation of sustainable reimbursement models 37,47,48 . One pilot study in England where patients had to pay out of pocket for pharmacist UTI testing and treatment service that they could have received at a national healthcare system clinic free of charge found that the majority of patients who were tested and received treatment would have gone to their general practitioner if the pharmacy service was not available 49 .…”
Section: Economic and Humanistic Outcomesmentioning
confidence: 99%
“… 7 Further evidence of cost savings of pharmacist prescribing for minor ailments was identified in a recent modelling study from Ontario, Canada, that projected savings of $4.08 to $7.51 per patient depending on the minor ailment. 8 Despite the well documented benefits of pharmacist prescribing, implementation has been lower than expected. 9 …”
Section: Introductionmentioning
confidence: 99%